Question
upstudy study bank question image url

Write the equation of a hyperbola with the follow- ing characteristics: Vertices: \( (-2,9) \) and \( (-2,-7) \) Asymptotes: \( y-1= \pm \frac{4}{3}(x+2) \)

Ask by Mitchell Fitzgerald. in the United States
Jan 31,2025

Upstudy AI Solution

Tutor-Verified Answer

Answer

The equation of the hyperbola is \(\dfrac{(y - 1)^2}{64} - \dfrac{(x + 2)^2}{36} = 1\).

Solution

To find the equation of the hyperbola with the given characteristics, let's break down the information step by step. ### Given: - **Vertices:** \((-2, 9)\) and \((-2, -7)\) - **Asymptotes:** \(y - 1 = \pm \frac{4}{3}(x + 2)\) ### Step 1: Determine the Center The center \((h, k)\) of the hyperbola is the midpoint of the vertices. \[ h = \frac{-2 + (-2)}{2} = -2 \] \[ k = \frac{9 + (-7)}{2} = 1 \] So, the center is \((-2, 1)\). ### Step 2: Find the Distance Between the Center and Vertices (a) The distance \(a\) from the center to each vertex along the transverse axis (vertical in this case) is: \[ a = 9 - 1 = 8 \] ### Step 3: Determine the Slope of the Asymptotes and Find b The asymptotes for a vertical hyperbola are given by: \[ y = k \pm \frac{a}{b}(x - h) \] Comparing this with the given asymptotes \(y - 1 = \pm \frac{4}{3}(x + 2)\), we can identify: \[ \frac{a}{b} = \frac{4}{3} \implies \frac{8}{b} = \frac{4}{3} \implies b = 6 \] ### Step 4: Write the Standard Equation For a vertical hyperbola, the standard form is: \[ \frac{(y - k)^2}{a^2} - \frac{(x - h)^2}{b^2} = 1 \] Substituting the values we found: \[ \frac{(y - 1)^2}{8^2} - \frac{(x + 2)^2}{6^2} = 1 \] \[ \frac{(y - 1)^2}{64} - \frac{(x + 2)^2}{36} = 1 \] ### Final Equation: \[ \boxed{\dfrac{(y - 1)^2}{64}\ -\ \dfrac{(x + 2)^2}{36}\ =\ 1} \]

Answered by UpStudy AI and reviewed by a Professional Tutor

error msg
Explain
Simplify this solution

The Deep Dive

To write the equation of the hyperbola, we start with the given vertices at \( (-2, 9) \) and \( (-2, -7) \). The center of the hyperbola can be found by averaging the y-coordinates of the vertices: \[ \text{Center} = \left(-2, \frac{9 + (-7)}{2}\right) = (-2, 1). \] The distance between the vertices is \( 16 \) (from \( 9 - (-7) = 16 \)), so \( 2a = 16 \) gives \( a = 8 \). This hyperbola opens vertically (because the vertices have the same x-coordinate), so we have: \[ \frac{(x + 2)^2}{b^2} - \frac{(y - 1)^2}{64} = -1. \] Next, we find \( b \) using the slopes of the asymptotes \( \pm \frac{4}{3} \). Recall that for hyperbolas, the asymptotes are given by: \[ y - k = \pm \frac{a}{b}(x - h), \] which in this case refers to the slopes being \( \pm \frac{8}{b} \), equating \( \frac{8}{b} = \frac{4}{3} \), gives \( b = 6 \). Therefore, the \( b^2 = 36 \) value can be plugged into the equation. Thus, the complete equation of the hyperbola is: \[ \frac{(x + 2)^2}{36} - \frac{(y - 1)^2}{64} = -1. \] Now, you’ve got a beautifully crafted hyperbola equation!

Related Questions

Latest Geometry Questions

Try Premium now!
Try Premium and ask Thoth AI unlimited math questions now!
Maybe later Go Premium
Study can be a real struggle
Why not UpStudy it?
Select your plan below
Premium

You can enjoy

Start now
  • Step-by-step explanations
  • 24/7 expert live tutors
  • Unlimited number of questions
  • No interruptions
  • Full access to Answer and Solution
  • Full Access to PDF Chat, UpStudy Chat, Browsing Chat
Basic

Totally free but limited

  • Limited Solution
Welcome to UpStudy!
Please sign in to continue the Thoth AI Chat journey
Continue with Email
Or continue with
By clicking “Sign in”, you agree to our Terms of Use & Privacy Policy